Lead Halide Post‐Perovskite‐Type Chains for High‐Efficiency White‐Light Emission. Issue 14 (18th February 2019) - Gautier, Romain; Massuyeau, Florian; Galnon, Gabin; Paris, Michael
Abstract: Hybrid metal halides containing perovskite layers have recently shown great potential for applications in solar cells and light‐emitting diodes. Such compounds exhibit quantum confinement effects leading to tunable optical and electronic properties. Thus, broadband white‐light emission has been observed from diverse metal halides and, owing to high color rendering index, high thermal stability, and low‐temperature solution processability, these materials have attracted interest for application in solid‐state lighting. However, the reported quantum yields for white photoluminescence (PLQY) remain low (i.e., in the range 0.5–9%) and no approach has shown to successfully increase the intensity of this emission. Here, it is demonstrated that the quantum efficiencies of hybrid metal halides can be greatly enhanced if they contain a polymorph of the [PbX4 ] 2− perovskite‐type layers: the [PbX4 ] 2− post‐perovskite‐type chains showing a PLQY of 45%. Different piperazines lead to a hybrid lead halide with either perovskite layers or post‐perovskite chains influencing strongly the presence of self‐trapped states for excitons. It is anticipated that this family of hybrid lead halide materials could enhance all the properties requiring the stabilization of trapped excitons. Abstract : A new hybrid lead halide material built of deformable post‐perovskite‐type chains exhibits an enhanced intrinsic white photoemission, setting a new record of 45% for photoluminescence quantum yield. The deformable lattice of this compound enables the self‐trapping of excitons responsible for broadband emission.